Upaya Meningkatkan Kemampuan Mengenal Huruf Hijayyah pada Anak Usia Dini melalui Permainan Dadu di KB Permata Ibu Desa Tanjung Kecamatan Koto Kampar - Aswira Wengsi; Rahmah Rahmah; Suparmi Suparmi (Asian Journal of Early Childhood and Elementary Education, 2026)
The ability to recognize hijaiyah letters is an important foundation for language development and religious education in early childhood. However, observations at KB Permata Ibu in Tanjung Village revealed that the learning process still faced several challenges, particularly the limited use of engaging instructional media and children’s low interest in recognizing hijaiyah letters. This study aimed to improve early childhood learners’ ability to recognize hijaiyah letters through the use of a dice game as a learning medium. The study employed a classroom action research design conducted in two cycles, involving 15 children aged 4–5 years at KB Permata Ibu, Tanjung Village. Data were collected through observation and documentation and were analyzed using percentages. The findings showed that the children’s ability to recognize hijaiyah letters improved in each cycle, increasing from 45.44% in the first meeting of Cycle I to 61.38% in the second meeting, then rising further in Cycle II to 71.13% in the first meeting and reaching 81.58% in the second meeting, categorized as developing very well. These findings indicate that the use of the dice game was effective in improving children’s ability to recognize hijaiyah letters. The study implies that game-based instructional media can enhance children’s motivation, concentration, and interest in learning, thereby making the process of recognizing hijaiyah letters more enjoyable and interactive.